Evaluation of the Master of curriculum and science instruction in Taibah University in the light of (CAEP) Standards - Almatrafi, Rashdan Humaid; Alahmadi, Sawsan Nasser (Journal of Educational and Psychological Sciences, 2020)
This study aimed to evaluate the master program of curriculum and science instruction in Taibah University in the light of the standards of council for the accreditation of educator preparation (CAEP). To achieve that, the study applied a questionnaire on the research population that consisted of all the faculty members (7) in the curriculum and science instruction specialty. And all the students (7) in the curriculum and science instruction specialty. The questioner consisted of (32) items distributed on the (CAEP) five standards: Content and Pedagogical Knowledge, Clinical Partnerships and Practice, Candidate Quality and Selectivity, Program Impact, Provider Quality Assurance and Continuous Improvement. The results showed that (CAEP) standards are highly available in the program with an average of (3.46) where: Content and Pedagogical Knowledge comes first with an average of (3.67) then Candidate Quality and Selectivity (3.51), Program Impact (3.45), Clinical Partnerships and Practice (3.41), and they all were highly available. And in the last place Provider Quality Assurance and Continuous Improvement (3.08) with a medium availability in the program. And the results showed that There were no significant differences at the level of significance(α≤0.05) between the faculty members and students responds of (CAEP) standards availability in the program. The study recommended prepare the curriculum and science instruction specialty to import (CAEP) standards. and perform more studies about (CAEP) standards.